(untitled) (Revista de Artes Marciales Asiáticas, 2020)
Objective: To investigate the effects of the addition of a specific high-intensity intermittent training (HIIT) protocol to the habitual training on the physical fitness of amateur wushu sanda athletes. Methods: This is an experimental study in which 6 amateur regional level wushu sanda athletes (24.6±6.4 yrs, 1.70±0.1m height, and 71.3±7.3kg weight) underwent a 2 session/week training program for 4 weeks. The HIIT specific protocol was composed of 3 rounds of 2 minutes with 1-minute intervals in between, simulating a match duration. Each round was divided into 8 blocks of 15 seconds. Each block was composed of 5 seconds of high-intensity activities, 5 seconds of low-intensity activities and 5 seconds of pause. Countermovement jump, squat jump, horizontal jump, aerobic fitness (TKDtest) and kick speed test (FSOK) were applied. Results: Athletes presented performance increases in countermovement jump (from 41±5.7 to 47.3±7.3cm, p=0.007, g=0.88), horizontal jump (from 1.7±0.4 to 2.3±0.3cm, p=0.01, g=1.56) and in the FSOK test (from 19.8±1.7 to 23.0±2.5 kicks, p=0.003, g=1.38). The resting heart rate decreased (from 120±8.3 to 107±11.4 bpm, p=0.03, g=1.20) and the time to exhaustion increased (from 8.5±1.8 to 13.1±1.4 min, p=0.003, g=2.63), as well as the number of kicks (from 187±55.3 to 368±39.8 kicks, p=0.001, g=3.46). Conclusion: Despite the small sample size, the large effect sizes found support the conclusion that the addition of a specific HIIT wushu sanda protocol to amateur athletes’ training routine can lead to neuromuscular, aerobic and anaerobic performance improvements.